THE IMPLEMENTATION ONLINE AND OFFLINE LEARNING STRATEGIES IN INDONESIAN SENIOR HIGH SCHOOL DURING THE COVID-19 PANDEMIC - Nurdin, Nurmalahayati; Kadir, Muhammad Ya’kub Aiyub; Sipahutar, Amlisa Mutiandini; Sipahutar, May Sintia; Ardiansyah, M Edo; Fuadi, Zahrul; Diana, Nasri (UIN AR-RANIRY, 2024)
The world was very surprised by the existence of a new virus variant originating from China which we are usually familiar with as the Covid-19 Virus Variant. The Covid-19 virus is a threat to all corners of the world, this virus has forced the world to experience a global pandemic for the past few years. This type of research is a quantitative research type with data collection using a questionnaire. The methodology used in collecting research data this time was a survey of various teachers at high school of the same level in the cities of Banda Aceh and Aceh Besar. The purpose of using the survey method is to obtain accurate data on a group that is not limited to demographic information and is able to collect attitudes and beliefs in a population. This study used a data collection technique using random sampling consisting of 160 participants (23 men and 137 women) consisting of all teachers and school management in several high school schools in Banda Aceh and Aceh Besar. Online learning is also supported by students, teachers, school facilities and infrastructure that are ready to implement changes to the learning system imposed by the government. This is also supported by school facilities and infrastructure where schools already have good computers and have internet access that can be used in the online learning process